Bolsonaro, Kast e Milei: un “nuovo populismo” in America Latina? (Nuovi Autoritarismi e Democrazie: Diritto, Istituzioni, Società (NAD-DIS), 2025)
Bolsonaro, Kast and Milei: a “new populism” in Latin America?In recent years, Latin America has witnessed the emergence of seemingly “new” political phenomena. This refers to Jair M. Bolsonaro in Brazil, José Antonio Kast in Chile, and Javier G. Milei in Argentina, who have become central figures in the region. This essay aims to analyze the evolution of the political cultures of these leaders through the lens of populism. By focusing on these three cases in particular, the paper aims to understand the ways in which a further hybridization –and thus transformation– of populism is taking shape in Latin America. Starting from the study of the practices and political discourse of these leaders, this essay seeks to contribute an additional perspective to populism studies, moving beyond the traditional right vs. left dichotomy.
Keywords: Populism; Javier G. Milei; Jair M. Bolsonaro; José A. Kast; Latin America